Charge compensation and solid-state lighting application for dysprosium-activated Ba2TeP2O9 phosphor - Song, Ruitong; Zheng, Youkui; Li, Hong; Mao, Yong; Xiong, Kai; Zhu, Jing (Journal of alloys and compounds, 2022)
In this study, trivalent dysprosium (Dy3+) activators were doped into barium tellurooxyphosphate Ba2TeP2O9 (BTP) by a solid-state sintering procedure, where alkali metal (A = Li, Na, and K) ions co-doped as charge compensator were aimed at improving the luminescent performance. To investigate optical absorption behavior, the electronic structure of the BTP host was realized via the density functional theory (DFT) method. The BTP:Dy3+ phosphor excited by 349 nm shows bright yellow emission. When the concentration of the Dy3+ activator is greater than 0.03 mol, concentration quenching occurs owing to dipole–dipole interaction. After doping 0.03 mol A+ ions into the BTP:0.03Dy3+ phosphor, the emission intensity of BTP:0.03Dy3+ enhances by 1.18 (Li+), 1.43 (Na+), and 2.32 times (K+). Additionally, the BTP:0.03Dy3+,0.03 K+ phosphor exhibits satisfactory thermal stability. A white light-emitting diode (w-LED) was successfully fabricated from the BTP:0.03Dy3+,0.03 K+ and commercial blue phosphors with a 365 nm LED chip. The study reveals that the BTP:0.03Dy3+,0.03 K+ phosphor is a prospective yellow-emitting candidate for w-LED. •Due to the asymmetric coordination of Dy3+, the yellow-emitting of BTP:Dy3+ is stronger than its blue-emitting. •Co-doping K+ into the host can both produce minimal lattice distortion and reduce the structural vacancy. •The thermostability of BTP:0.03Dy3+,0.03 K+ is competitive with that of the commercial yellow phosphor.•The concentration quenching mechanism is the dipole–dipole interaction.